The behavioral advantage : what the smartest, most successful companies do differently to win in the B2B arena - Bacon, Terry R. (AMACOM, 2004)
In their book Winning Behavior, Terry Bacon and David Pugh showed how great companies outperform good ones through "behavioral differentiation"--Going beyond superior products and dependable service to connect with customers at every touchpoint. The Behavioral Advantage broadens the concept, applying behavioral differentiation to the business-to-business arena. The best B2B companies depend on a multifront approach to business interaction, and The Behavioral Advantage reveals the secrets behind what is essentially a chess game with competitors. To win the game, companies must develop a carefully plotted opening game, with all internal values, policies, practices, and behaviors fully aligned. A smart and efficient middle game lets the company build and strengthen its position, and the endgame assures victory and lays the groundwork for future business. Just as individual customers do, B2B customers remember those companies whose behavior consistently and significantly outshines even strong competitors. These firms create a lasting advantage -- and reap the profits that come with it